2022
DOI: 10.1002/glia.24234
|View full text |Cite
|
Sign up to set email alerts
|

Microglial response promotes neurodegeneration in the Ndufs4 KO mouse model of Leigh syndrome

Abstract: Leigh syndrome is a mitochondrial disease characterized by neurodegeneration, neuroinflammation, and early death. Mice lacking NDUFS4, a mitochondrial complex I subunit (Ndufs4 KO mice), have been established as a good animal model for studying human pathology associated with Leigh syndrome. As the disease progresses, there is an increase in neurodegeneration and neuroinflammation, thereby leading to deteriorating neurological symptoms, including motor deficits, breathing alterations, and eventually, death of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…The findings in this study are consistent with recent work by the Hidalgo laboratory, and our own prior work, demonstrating that low dose pexidartinib, used to eliminate microglia while sparing peripheral macrophages, only modestly alters disease course in the Ndufs4(KO) [1,24]. These data indicate that microglia contribute only partially to the pathogenesis of LS and that targeting microglia alone is insufficient to disrupt disease.…”
Section: Discussionsupporting
confidence: 91%
“…The findings in this study are consistent with recent work by the Hidalgo laboratory, and our own prior work, demonstrating that low dose pexidartinib, used to eliminate microglia while sparing peripheral macrophages, only modestly alters disease course in the Ndufs4(KO) [1,24]. These data indicate that microglia contribute only partially to the pathogenesis of LS and that targeting microglia alone is insufficient to disrupt disease.…”
Section: Discussionsupporting
confidence: 91%
“…CSF1R inhibition rescued disease, including both a complete prevention of CNS lesions and a rescue of peripheral symptoms such as metabolic dysfunction and cachexia [112]. Very recently, the partial benefits provided by low doses of PLX3397 have been independently reproduced by another group [116]. Together, these data provide strong evidence that LS is an immune-mediated disease.…”
Section: Pre-clinical Studiesmentioning
confidence: 83%
“…Along these lines, we should note that two recent studies reported that treatment of germline ndufs4 − / − mice with the colony stimulating factor-1 receptor (CSF1R) inhibitor pexidartinib resulted not only in depletion of Iba1 + mononuclear cells but also in suppression of brain lesion formation, reduction of neurological dysfunction, and prolongation of the lifespan of the mice. 39 , 68 These findings suggest that combatting inflammation can be neuroprotective in the setting of complex I dysfunction. Future studies in our mouse model testing whether the combination of anti-inflammatory interventions with hypoxia may result in additive or even synergistic RGC neuroprotection would therefore be very interesting.…”
Section: Discussionmentioning
confidence: 98%